Effects of Dietary Bamboo Charcoal Powder Including Vinegar Liquid on Growth Performance and Histological Intestinal Change in Aigamo Ducks - Ruttanavut, J.; Yamauchi, K.; Goto, H.; Erikawa, T. (International Journal of Poultry Science, 2009)
To investigate effects of a mixture of bamboo charcoal powder and bamboo vinegar solution (SB) on growth performance and histological intestinal change, 48 mixed sex Aigamo ducks were fed the basal commercial diet supplemented with SB at 0, 0.1 and 1% ad libitum for 49 days. Although, feed intake, weight gain and feed efficiency were not significantly different, the growth performance tended to be improved with increasing dietary SB. In these birds, also the intestinal villus height, villus area, epithelial cell area and cell mitosis in all intestinal segments tended to be increased with increasing dietary SB and increased in 1% dietary group (p